CD4+ T-cell, CD8+ T-cell, CD4+ /CD8+ ratio, and apoptosis as a response to induction phase chemotherapy in pediatric acute lymphoblastic leukemia - May Fanny Tanzilia; Andi Cahyadi; Yetti Hermaningsih; Endang Retnowati; I Dewa Gede Ugrasena (Paediatrica Indonesiana, 2017)
Background Acute lymphoblastic leukemia (ALL) is a neoplastic disease resulting from somatic mutation in the lymphoid progenitor cells, often occuring in children aged 2-5 years, predominantly in males. Results from the induction phase of chemtherapy are used to measure success, but the failure remission rate is still high. Increased apoptosis of cancer cells, as induced by CD4+ and CD8+T-cells, is an indicator of prognosis and response to chemotherapy.Objective To assess for correlations between CD4+, CD8+, or CD4+/CD8+ ratio to the chemotherapy induction phase response (i.e., apoptosis) in pediatric ALL patients.Methods This observational analytical cohort study was done in 25 pediatric ALL patients. Whole blood (3 mL) with EDTA anticoagulant were used to measure absolute counts of CD4+, CD8+, and CD4+/CD8+ ratio. Peripheral blood mononuclear cells (PBMC) were examined for apoptosis. The principle of CD4+, CD8+ examination was bond between antigens on the surface of the leukocyte in the blood with fluorochrome labeled antibodies in the reagents, while the principle of apoptosis examination was FITC Annexin V will bonds with phosphatidylserine that moves out of the cell when the cell undergoes apoptosis, then intercalation with propidium iodide (PI). All examination were detected by flow cytometry BD FACSCalibur.Results Subjects were 25 newly-diagnosed, pediatric ALL patients (64% males and 36% females). Most subjects were 3 years of age (20%). Numbers of CD4+ and CD8+ cells, as well as CD4+/CD8+ were significantly decreased after chemotherapy. However, apoptosis was not significantly different before and after chemotherapy (P=0.689), There were significant negative correlations between apoptosis and CD4+ (P=0.002; rs=-0.584), and CD8+ (rs=-0.556; P=0.004), before chemotherapy. In addition, CD4+-delta and apoptosis-delta also had a significant positive correlation (rs=0.478; P=0.016). However, no correlation was found between the CD4+/CD8+ ratio and apoptosis, before or after chemotherapy.Conclusion There are significantly lower mean CD4+, CD8+, and CD4+/CD8+ ratio after chemotherapy than before. Also, there are significant correlations between CD4+-delta and apoptosis-delta, as well as between apoptosis and CD4+, CD8+, and CD4+/CD8+, before chemotherapy. CD4+, CD8+, and CD4+/CD8+ can be used to predict apoptosis before chemotherapy. In addition, CD4+-delta can be used to predict apoptosis-delta as a response to induction phase chemotherapy in pediatric ALL.